MATHEMATICS TEACHER’S SELF-EFFICACY OF TECHNOLOGY INTEGRATION AND TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE - Bakar, Nurul Shahhida Abu; Maat, Siti Mistima; Rosli, Roslinda (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2020)
This study conducted to determine the mathematics teacher’s self-efficacy of technology integration and Technological Pedagogical Content Knowledge (TPACK) based on gender and teaching experience. In this research, 66 mathematics teachers from national secondary schools were chosen as the samples to answer a survey questionnaire containing 71 items with a five-point Likert scale. Descriptive statistics, such as mean, percentage, and standard deviation, were employed to analyze the data. T-test was used to gauge the mathematics teacher’s self-efficacy of technology integration and TPACK based on gender, and one-way ANOVA was employed to determine mathematics teacher’s self-efficacy of technology integration and TPACK based on teaching experience. Besides, Pearson’s correlation coefficient was used to determine the relationship between the mathematics teacher’s self-efficacy of technology integration and TPACK. The findings showed no significant difference between genders and the teaching experience of the mathematics teacher’s self-efficacy and TPACK. However, mathematics teacher’s self-efficacy of technology integration and TPACK were strongly associated. In conclusion, whether male or female, for as long as mathematics teachers had been working, they have a positive self-efficacy in initiating technology integration and introducing TPACK. The implication was gender and teaching experience were not a critical factor for mathematics teacher’s self-efficacy of technology integration and TPACK. For future research related to this study, it could introduce other factors, such as academic qualification and technology courses they had attended.